Talking Stick Model : Sebuah Pengaruh Dalam Melihat Hasil Belajar Siswa - Suhirman Suhirman; Agus Wedi (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
Abstract: Talking Stick Model: An Influence In Seeing Student Learning Outcomes.Variations in learning need to be done to adjust to the latest student conditions. The purpose of this study was to determine the effect of the talking stick learning model on the learning outcomes of Islamic Religious Education for grade 5 students at SDN 10 Sungai Are, OKU Selatan District, for the 2021/2022 academic year. The method is quantitative with a Quasi Experimental Design approach. The population in this study amounted to 28 students. The data collection technique in this study was a learning achievement test in the form of multiple choice of 20 questions which had previously been tested for validity and reliability. The results of the calculation of the learning outcomes test are 19 valid questions and 1 invalid question. The data analysis technique used is the normality test, homogeneity test, and hypothetical test using paired sample t-tests. Based on the research results, there are learning outcomes of Islamic Religious Education before and after using the talking stick learning model. this is evidenced by the results of the paired t-test which shows a sig.(2 tailed) value of 0.582 where the value is smaller than the value of 0.05. Thus the results of this study can be seen that the use of the talking stick learning model can improve learning outcomes significantly.Abstrak: Talking Stick Model : Sebuah Pengaruh Dalam Melihat Hasil Belajar Siswa.Variasi dalam pembelajaran perlu dilakukan untuk menyesuaikan kondisi siswa yang terbaru. Tujuan studi ini untuk mengetahui pengaruh model pembelajaran talking stick terhadap hasil belajar Pendidikan Agama Islam siswa kelas 5 di SDN 10 Sungai Are Kabupaten OKU Selatan tahun ajaran 2021/2022. Metodenya adalah kuantitatif dengan pendekatan Quasi Experimental Design. Populasi dalam penelitian ini berjumlah 28 peserta didik. Teknik pengumpulan data dalam penelitian ini adalah tes hasil belajar dalam bentuk pilihan ganda sebanyak 20 soal yang terlebih dahulu telah diuji validitas dan reabilitasnya. Hasil perhitungan tes hasil belajar adalah 19 soal valid dan 1 soal tidak valid. Teknik analisis data yang digunakan adalah uji normalitas,uji homogenitas,dan uji hipotetis dengan menggunakan paired sampe t-tes. Berdasarkan hasil penelitian terdapat hasil belajar Pendidikan Agama Islam sebelum dan sesudah menggunakan model pembelajaran talking stick. hal ini dibuktikan dari hasil uji paired t-test yang menunjukan nilai sig.(2 tailed) sebesar 0,582 dimana nilai lebih kecil dari nilai 0,05. Dengan demikian hasil penelitian ini dapat dilihat bahwa penggunaan model pembelajaran talking stick dapat meningkatkan hasil belajar secara signifikan.